Outcomes of coronary artery aneurysms: insights from the Coronary Artery Ectasia and Aneurysm Registry (CAESAR) - Alessandro Candreva; Jessica Huwiler; Diego Gallo; Victor Schweiger; Thomas Gilhofer; Roberta Leone; Michael Würdinger; Maurizio Lodi Rizzini; Claudio Chiastra; Julia Stehli; Jonathan Michel; Alexander Gotschy; et al. (Swiss Medical Weekly)
BACKGROUND: Coronary artery ectasias and aneurysms (CAE/CAAs) are among the less common forms of coronary artery disease, with undefined long-term outcomes and treatment strategies.